How to Escape the Dictatorship of Covid-19? - Luce Irigaray (The European Journal of Psychoanalysis, 2021)
A few remarks to give back some hope to those who suffer from the dictatorship of the virus and the powerless passivity they are enduring because of it. They suggest that there are potentialities that we can explore not only for our survival but for clearing the way towards a more fulfilled life still unknown to us. They also address the psychoanalysts calling on them to consider the resources of sexuate, and not merely sexual, difference for the existence of each and the evolution that our humanity must achieve.
Keywords: immunity; breathing; touch; sexuate difference; cultivation of energy